Research Methods for the Digital Humanities (Springer International Publishing, 2018)
This volume introduces the reader to the wide range of methods that digital humanities employ, and offers a practical guide to the study, interpretation, and presentation of cultural material and practices. In this instance, the editors consider digital humanities to include both the use of computing to understand cultural material in new ways, and the application of theories and methods from the humanities to interpret new technologies. Each chapter provides a step-by-step guide to cutting-edge methodologies so that students can make informed decisions about the methods they use, consider ethical practices, follow practical procedures, and present their work effectively. Readers will develop practical and reflexive understandings of the software and digital devices that they study and use for research, and the book will help new researchers collaborate and contribute to their scholarly communities, and to public discourse. As contemporary humanities work becomes increasingly interdisciplinary, and increasingly permeated by and with digital technologies, this volume helps new researchers navigate an evolving academic environment. Humanities and social sciences students will find this textbook an invaluable resource for assessing and creating digital projects.